Cross-generational acceptance of and interest in advanced vehicle technologies: A nationwide survey. (November 2015) - Owens, Justin M.; Antin, Jonathan F.; Doerzaph, Zachary; Willis, Susan
Highlights: Surveyed drivers across generations about attitudes toward advanced and connected vehicle systems. 1019 drivers between the ages of 18 and 85 were surveyed from across the United States. Generations showed differences in experience and interest in advanced in-vehicle technology. Older generations had less enthusiasm for vehicle technology but exhibited willingness to engage. We discuss implications for emerging connected vehicle systems in context of an aging population. Abstract: The number of older drivers on the roadways is increasing; at the same time, technology in the automotive environment is rapidly evolving. To investigate the potential impact of these converging changes, this study used a cross-generational approach to compare driver attitudes toward advanced automotive technologies. Approximately 1000 drivers between the ages of 18 and 85 located across the United States responded to a survey about their opinions regarding general technology, advanced in-vehicle technology, and near-horizon connected vehicle systems. Participant responses were categorized using a generational construct, sorting responses not only by age but by shared life experiences (e.g. economic circumstances, involvement in wartime activities, cultural movements, etc.). The oldest generation (the "Silent" generation) exhibited the least interest in and comfort with advanced technology, although they owned and used advanced in-vehicle technology at approximately the same rates as the two middle generations. The youngest generation (the "Millennial" generation) was most likely to be interested in and comfortable with technology, but was least likely to own vehicles with advanced technology. All participants expressed interest in safety-related connected vehicle systems, but less so in infotainment applications. Reservations regarding data security and system cost were shared across generations. These findings are framed in the context of an aging population with unique driving and vehicle needs, and provide information that may assist both with vehicle technology design aspects and the proposed large-scale implementation of connected vehicle systems, including considerations for seniors and emphasis on safety systems and data security.